Neo-neoliberalist capitalism, intensification by stealth and campus real estate in the modern university in Aotearoa/New Zealand (Journal of Applied Learning and Teaching, 2023)
This article critiques media commentary on reforms in higher education (HE) and the polytechnic or vocational education and training (VET) in Aotearoa/New Zealand during 2023. It used as its epicentre Gaston’s (2023) opinion piece, particularly on the current round of redundancies, rationalisations and restructurings in the sector in our ‘post-COVID-19’ world. Her suggestion that the reforms as we see them today lead me to explore the origins of neoliberalist ideology in tertiary education in the country, seeking a definition to guide how Aotearoa/New Zealand, in particular, has experienced and manifested neoliberalist policy. The ideology’s emphasis on work intensification and responsibilisation at both the level of the individual and the organization lies at the heart of the rationale. Since 2023 has been a year of mysterious budget holes for many universities and for the emergent super-Polytechnic Te Pūkenga/New Zealand Institute of Skills and Technology, I investigate how the media and public domain materials report the financial state of our tertiary providers. Generating a case study of the University of Otago’s property portfolio, which grew by two billion dollars between 2012 and 2022, I tap into recent critiques of the university as a real estate portfolio and campus as literally ‘flat land’ that has the potential to become a domain less in the name of education than neoliberalist capitalism.